Atomic‐Precision Tailoring of Au–Ag Core–Shell Composite Nanoparticles for Direct Electrochemical‐Plasmonic Hydrogen Evolution in Water Splitting. (19th May 2021) - Mo, Jiaying; Barbosa, Eduardo C. M.; Wu, Simson; Li, Yiyang; Sun, Yuancheng; Xiang, Weikai; Li, Tong; Pu, Shengda; Robertson, Alex; Wu, Tai‐sing; Soo, Yun‐liang; Alves, Tiago V.; et al.
Abstract: Traditionally, bandgap materials are a prerequisite to photocatalysis since they can harness a reasonable range of the solar spectrum. However, the high impedance across the bandgap and the low concentration of intrinsic charge carriers have limited their energy conversion. By contrast, metallic nanoparticles possess a sea of free electrons that can effectively promote the transition to the excited state for reactions. Here, an atomic layer of a bimetallic concoction of silver–gold shells is precisely fabricated onto an Au core via a sonochemical dispersion approach to form a core–shell of Au–Ag that exploits the wide availability of excited states of Ag while maintaining an efficient localized surface plasmon resonance (LSPR) of Au. Catalytic results demonstrate that this mix of Ag and Au can convert solar energy to hydrogen at high efficiency with an increase of 112.5% at an optimized potential of −0.5 V when compared to light‐off conditions under the electrochemical LSPR. This outperforms the commercial Pt catalysts by 62.1% with a hydrogen production rate of 1870 µmol g −1 h −1 at room temperature. This study opens a new route for tuning the range of light capture of hydrogen evolution reaction catalysts using fabricated core–shell material through the combination of LSPR with electrochemical means. Abstract : An atomically thin bimetallic‐layered core–shell nanoparticle is synthesised via sonochemical dispersion. The Au–Ag shell gives rise to a localized surface plasmon resonance effect that transits hot electrons into a low‐lying excited state for efficient proton reduction with the aid of sunlight, which outperforms commercial Pt and gives an excellent hydrogen production rate of 1870 µmol g −1 h −1 at room temperature.